Unveiling early stage autoimmune gastritis: novel endoscopic insights from two case reports - Yu, Yunfeng; Shangguan, Xueli; Yu, Rong; Wu, Yangpeng; Xu, En; Tan, Chuanchuan (Frontiers in Immunology, 2024)
The predominant characteristic of autoimmune gastritis (AIG) is corpus-dominant advanced atrophy, which is mostly observed in the middle to late stages. More reports are needed on the endoscopic features of the early stage. In this report, we present two cases of early-stage AIG in which endoscopic examinations showed no atrophy of the gastric mucosa but displayed a transition of collecting venules from a regular to an irregular arrangement. In addition, yellowish-white cobblestone-like elevations were observed in the fundic gland region. Histologically, the observed manifestations included pseudohypertrophy and protrusion of parietal cells into the lumen, possibly along with hyperplasia of G cells, lymphocytic infiltration and potentially pseudopyloric gland metaplasia. Serologically, the anti-parietal cell antibody returned positive results, whereas the anti-intrinsic factor antibody yielded negative results. In this study, we summarized some endoscopic features of two patients, aiming to provide clues for endoscopists to detect early-stage AIG.